Biological activities of phenolic compounds isolated from galls of Terminalia chebula Retz. (Combretaceae) - Aranya Manosroi (2018)
The aqueous extract of galls from Terminalia chebula Retz. (Combretaceae) was fractionated on Diaion and refractionated on octadecyl silica column. Six phenolic compounds were isolated and identified as gallic acid (1), punicalagin (2), isoterchebulin (3), 1,3,6-tri-O-galloyl-β-D-glucopyranose (4), chebulagic acid (5) and chebulinic acid (6). All of the compounds showed stronger 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and melanin inhibitory activities than ascorbic acid, butylated hydroxytoluene, α-tocopherol, arbutin and kojic acid, the reference compounds. Gallic acid (1) exhibited inhibitory activity against nitric oxide production in lipopolysaccharide-activated macrophages. However, all isolated compounds exhibited less activity than the reference compounds in mushroom tyrosinase inhibition and human tumour cytotoxicity assays. This study has demonstrated that the phenolic compounds isolated from galls of T. chebula might contribute significantly due to their antioxidant and whitening activities. © 2010 Taylor & Francis.